ETHICAL TEACHINGS IN THE HOLY QURAN AND ESTABLISHMENT FOR CIVILIZATION - Qasim, Israa Abdul-Jabbar; Al-Muhammadi, Hussein Abd (Al-Adab Journal, 2022)
The Holy Quran is taken for a great reference of ethical sciences. Although scholars and Quranic exegetes have studied carefully the Quranic researches on ethics, all such studies and researches have not yet touched on the method of connecting the Quranic ethical teachings with the topic of establishment for civilization and the topic of the direct interconnection between ethics and history. In all of its doctrinal, legal and ethical teachings, Islam creates emphatically a link between word, deed, value and practical attitude. Ethical teachings in Islam represent the common thread running through all fields of life, including the political, social and cultural. The current study, entitled: ‘Ethical Teachings in the Holy Quran and Establishment for Civilization,’ aims at demonstrating the role played by ethics in the process of building a human civilization. Without doubt, ethics and its items have their own operative effect on the reality of man’s social life, both the material and the mental. This is so because any true human life in any human society that is deprived of morals will definitely be lacking the true meaning of humanity. History has recorded that many bygone human communities were destined to ruin and then fading out once their individuals committed ethical perversions. Unless the individuals of a human community abide by moral values, they will unquestionably have to face hurtful termination. As they lose their ethical values, human nations lose therewith all viabilities of survival. Laws alone cannot meet even the basic needs of man who, consequently, will experience states of depression, spiritual emptiness and lack of incentives of living decent life. Activation of laws without there being a solid foundation of ethical values to be enjoyed by individuals is impossible. It is clear that unless there is prime mover created in the selves of individuals, all man’s exterior efforts are worthless. Therefore, there must be an ethical-behavioral criterion through which human societies hang on to human values in the selves in their individuals. Human values are enough to build sound societies and put right all material and mental breaches that may be found in the mentalities of their individuals. The current thesis deals, yet somewhat briefly, with three main topics. The first topic deals with the meanings, concepts, and basics of ethical teachings, while the second topic is concerned with the meanings, concepts and basics of civilization. As for the third topic, it is dedicated to explaining the morals and their role in the establishment for civilization.